Judical review of the rights of the ex-wife due to divorce associated with article 149 compilation of islamic law (decision study number: 624.Pdt.G/2021/Pa.Krw) - Irma Yuningsih; Yuniar Rahmatiar; Muhammad Abas; Lia Amaliya (The International Journal of Politics and Sociology Research, 2023)
In Islam, divorce is most commonly known as talak. Divorce is a husband's statement to separate from his wife that can be done formally (according to sharia law) or informally (kinayah). Divorce can be seen as a husband formally asking his wife for a divorce. A woman who is divorced from her husband is the one who is undergoing the iddah period, not the man or her husband. A woman must undergo an iddah period whether she is divorced from her husband or not in any way, whether she lives or dies, whether she is pregnant or not, and whether she is menstruating or not. According to the Law on Marriage and Compilation of Islamic Law, this study aims to find out the judge's considerations in Case Number: 624.Pdt.G/2021/Pa.Krw and women's rights after divorce. This essay uses a normative legal writing style. Normative juridical is used to collect data, analyze it, and investigate secondary materials in the form of laws and regulations, legal doctrines, and other legal concepts. In this divorce case, the judge used Inkracht, or a decision with permanent legal force, based on the results of the examination in the judge's considerations, both the decision of the Religious Court, which was not appealed by cassation, and the decision of the High Religious Court, which was not appealed within the allotted time. Because there were still disputes between the petitioner and the respondent that could not be resolved as husband and wife or as a household, the factor of divorce was present.